Coalescence and counterflow of droplets on needle electrode with negative corona discharge. (1st March 2022) - Wang, Zutao; Li, Chuan; Xiao, Menghan; Wang, Pengyu; Zhang, Ming; Shi, Peng; Li, Jiawei; Li, Dingchen; He, Fuyou; Yang, Wendi; Yang, Yong; Yu, Kexun; et al.
Abstract: The coalescence of droplets on the discharge electrode surface in high humidity environments has rarely been studied, which may affect discharge characteristics. Meanwhile, directional transport of droplets is of great significance for many applications ranging from fluidic processing to thermal management. Here, corona discharge in a needle-plate electrode is adopted to explore the coalescence rule of droplets attached on the discharge electrode surface in a high-humidity environment, and to realize the counterflow of droplets. The experimental results show that the number of coalesced droplets on the needle electrode surface reaches the maximum under −7.5 kV at relative humidity ∼94% and ambient temperature ∼20 °C. When the applied voltage increases from −6 kV to −11 kV, the droplet moves up 2.76 mm in 5 s. The size of the attached droplet depends on the balance of coalescence and evaporation. The coalescence is mainly attributed to the dielectrophoretic force caused by the high electric field gradient. The evaporation is related to the ionic wind generated by the corona discharge. With regard to the counterflow phenomenon of the droplet, we speculate that the high concentration gradient of positive ions near the needle electrode provides a driving force for the negatively charged droplets. Meanwhile, the electrons and negative ions below the needle tip offer a repulsive force to the droplet. The shape and moving direction of the droplet attached to the needle surface can be manipulated by changing the voltage applied to the needle electrode, which shows the potential application value in realizing the self-cleaning of electrodes, liquid lenses and so on.